Electric power distribution engineering - Gönen, Turan (CRC Press, 2014)
PrefaceAcknowledgmentsAuthorDistribution System Planning and AutomationLoad CharacteristicsApplication of Distribution TransformersDesign of Subtransmission Lines and Distribution SubstationsDesign Considerations of Primary SystemsDesign Considerations of Secondary SystemsVoltage-Drop and Power-Loss CalculationsApplication of Capacitors to Distribution SystemsDistribution System Voltage RegulationDistribution System ProtectionDistribution System ReliabilityElectric Power QualityDistributed Generation and Renewable EnergyEnergy Storage Systems for Electric Power Utility SystemsConcept of Smart.